Reactions of some 2-tert-butoxy-1,3,2-dithiophosphinanes with benzaldehide - Fomin, V.N.; Smolenkov, Yu.Yu.; Vassilets, E.P.; Rozhkovoy, I. E. (KSU publ., 2012)
The article describes the interaction of 5-methylthio-, 5-N,N-dimethylamino-2-tert-butoxy-1,3,2-dithiophosphinanes and 2-tert-butoxy-1,3,2-dithiophosphinane with benzaldehyde. It has been given the comparative evaluation of reactivity of the phosphinanes studied. The conclusions about the effect of substituents at the 5th position on the phosphinanes reactivity were made on the basis of quantum-chemical calculations and experiment data.
Keywords: 2-tert-butoxy-1,3,2-dithiophosphinane; 1,2-dithiolanes; 5-N,N-dimethylamino-1,3,2-dithiophosphinane; 5-methylthio-1,3,2-dithiophosphinane